An Analogue of Grubbs Third‐Generation Catalyst with Fluorophilic Pyridine Ligands: Fluorous/Organic Phase‐Transfer Activation of Ring‐Closing Alkene Metathesis. Issue 1 (26th November 2015) - Balogh, Janos; Hlil, Antisar R.; Su, Haw‐Lih; Xi, Zhenxing; Bazzi, Hassan S.; Gladysz, John A.
Abstract: The title catalyst (H2 IMes)[3, 5‐NC5 H3 (CH2 CH2 Rf8 )2 ]2 (Cl)2 Ru(=CHPh) [H2 IMes=1, 3‐bis(2, 4, 6‐trimethylphenyl)‐4, 5‐dihydroimidazol‐2‐ylidene, Rf8 =(CF2 )7 CF3 ] was prepared from the fluorous pyridine 3, 5‐NC5 H3 (CH2 CH2 Rf8 )2 (2.1 equiv.) and the pyridine complex (H2 IMes)(NC5 H5 )2 (Cl)2 Ru(=CHPh). 3, 5‐NC5 H3 (CH2 CH2 Rf8 )2 was synthesized by a Heck reaction of 3, 5‐dibromopyridine and the fluorous alkene H2 C=CHRf8 [2.4 equiv.; Pd(OAc)2 (cat.), n ‐Bu4 N + Br − /NaOAc (2.0 equiv.)], followed by hydrogenation. The catalyst shows dramatic rate accelerations in the ring‐closing metatheses of α, ω‐dienes under fluorous/organic liquid/liquid biphasic conditions [e.g., perfluoro(methyldecalin)/CD2 Cl2 ] relative to rates under monophasic organic conditions (e.g., CD2 Cl2 ). These catalysts require initial dissociation of the pyridine ligands to generate the active species, which can either combine with an alkene (productive) or recombine with a pyridine (unproductive). In the case of (H2 IMes)[3, 5‐NC5 H2 (CH2 CH2 Rf8 )2 ]2 (Cl)2 Ru(=CHPh), fluorophilic 3, 5‐NC5 H3 (CH2 CH2 Rf8 )2 transfers to the fluorous phase, in accord with its CF3 C6 F11 /toluene partition coefficient [93.9:6.1 vs. 39.8:60.2 for (H2 IMes)[3, 5‐NC5 H3 (CH2 CH2 Rf8 )2 ]2 (Cl)2 Ru(=CHPh)], which decreases the fraction of unproductive events. Abstract : Kidnapped ligands : An analogue of Grubbs third‐generation alkene metathesis catalyst with a fluorous pyridine ligand exhibits faster RCM rates for a variety of substrates if employed under fluorous/organic liquid/liquid biphasic conditions as opposed to organic monophasic conditions. Rf8 =(CF2 )7 CF3, Mes=2, 4, 6‐trimethylphenyl.